2009
DOI: 10.3354/meps07726
|View full text |Cite
|
Sign up to set email alerts
|

An amphibious mode of life in the intertidal zone: aerial and underwater contribution of Chthamalus montagui to CO2 fluxes

Abstract: International audienceThe contribution of the intertidal barnacle Chthamalus montagui to CO2 fluxes via respiration and calcification was measured both in the air and underwater. The mean biomass of the species was 44.92 g ash-free dry weight (AFDW) m–2 on the coast of Brittany, France. Underwater respiration, determined from changes in dissolved inorganic carbon (DIC), fluctuated from 6.14 µmol g–1 h–1 in winter to 13.37 µmol g–1 h–1 in summer. The contribution of C. montagui respiration to DIC fluxes for an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…When assessed by a method similar to that in this study, this ratio was 14% for C. fornicata (Martin et al 2006) and only 3% for Chthamalus montagui (Clavier et al 2009) near the Bay of Brest. Using the calcimass method, Chauvaud et al (2003) found that 33% of the total carbon flux produced by P. amurensis in the San Francisco Bay was released by the production of CaCO 3 .…”
Section: Co 2 Contributionmentioning
confidence: 92%
See 2 more Smart Citations
“…When assessed by a method similar to that in this study, this ratio was 14% for C. fornicata (Martin et al 2006) and only 3% for Chthamalus montagui (Clavier et al 2009) near the Bay of Brest. Using the calcimass method, Chauvaud et al (2003) found that 33% of the total carbon flux produced by P. amurensis in the San Francisco Bay was released by the production of CaCO 3 .…”
Section: Co 2 Contributionmentioning
confidence: 92%
“…Simpfendorfer et al (1995) demonstrated that the strategies employed by these species are largely determined by their position in the intertidal zone. Barnacles, usually found in the upper part of the shore, have high rates of aerial respiration that can reach 100% of their underwater rates (Simpfendorfer et al 1995;Clavier et al 2009). Aerial respiration rates of bivalves in the mid-tide zone have been found to range from 30% to 87% of underwater respiration (Simpfendorfer et al 1995;Marsden and Weatherhead 1998;Huang and Newell 2002).…”
Section: Respirationmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiration and biocalcification of marine animals such as molluscs can be a source of CO 2 into the ecosystem and their role in the carbon cycle has been demonstrated in temperate environments (Chauvaud et al 2003, Clavier et al 2009, Lejart et al 2012, Mistri & Munari 2013. This contribution can be assessed empirically through oxygen respiratory fluxes converted to carbon using available respiratory quotients (Boucher & Clavier 1995) or by directly assessing carbon metabolism through respiration and calcification measurements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Hyas araneus from Svalbard, the barnacle Chtalamus montagui (Clavier et al 2009), and the crayfish Asthacus asthacus (Lahti 1988) displayed a temperaturedependent level of calcification. Ostracods (Herpetocypris intermedia), living between 13 and 20°C, also demonstrated a temperature-dependent calcification rate, with decreased moulting and calcification rates associated with reduced survival at the low end of the temperature range (Mezquita et al 1999).…”
Section: Discussionmentioning
confidence: 99%